Surgical mortality in an aneurysm population: effects of age, blood pressure and preoperative neurological state. Issue 10 (October 1980) - Fortuny, L A; Adams, C B; Briggs, M
Abstract : The mortality of 256 patients surgically treated for ruptured intracranial aneurysms was assessed with regard to age, systemic blood pressure on admission and preoperative neurological state. Increasing age, hypertension, and a poor neurological state (both singly and in combination) were found to influence surgical results dramatically. It is suggested that preoperative treatment of hypertension, and delay of operation in those patients aged over 50 years or hypertensive, as well as waiting for the neurological state to improve prior to operation, may lead to better results.